Kunstdiva versus Stimmediva Callas and Sutherland in Bellini’s Norma - Gunter, Leah (College of Music, 2019)
The focus of this dissertation is to analyse the balance between interpretative and vocal ability in bel canto opera, which is traditionally considered as the principal domain of the Stimmediva. The dissertation includes a survey of the characteristics of bel canto, Bellini’s contribution to it and the performance history of his opera Norma. Furthermore, it investigates the German differentiation between Kunstdiva and Stimmediva as exemplified by two major sopranos of the twentieth century, Maria Callas and Joan Sutherland. Callas’s performance of Norma is universally recognised as a watershed in the performance history of this role, and Sutherland is widely regarded as her most important immediate successor. Their distinct approaches to the scena from Act 1 of Norma are contrasted and compared. Three respondents were asked to evaluate recordings of this scena by these two artists with regard to style, technique and interpretation. Their responses are presented in table format, and a discussion of the insights that emerge from these form the final part of the dissertation. The conclusion notes the primacy of interpretative ability in the appreciation of vocal performance even within the bel canto style, but argues for a complete integration of dramatic and vocal skills in order to arrive at the ideal interpretation. Key words: Bel canto; Bellini; Callas; Casta diva; Fine al rito, e il sacro bosco…Ah! bello a meritorna; Kunstdiva; Norma; Scena; Sediziose voci; Stimmediva; Sutherland